The effect of nest box temperature on the breeding success of Pied Flycatchers (Ficedula hypoleuca) in northern Sweden - Boer, Jorina (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
Benefits in terms of breeding success might arise from selecting nest sites with warmer thermal conditions. These energetic gains can subsequently be invested in increased breeding success by both parents and their nestlings. This could be of increasing importance when breeding in colder climates, where lower temperatures can impose limits on breeding outcome. Forest restoration treatments (prescribed burning and gap cutting) previously carried out in our study area in northern Sweden have led to differences in temperature. Along this natural thermal gradient the relationship between temperature and breeding success of Pied Flycatchers (Ficedula hypoleuca) were studied. To test thermal effects of different life stages, temperature data was divided into the nesting (i), egg-laying (ii), incubation (iii) and nestling stage (iv). Results obtained in this study suggests that birds had mainly benefited from increased temperatures. Warmer temperatures led to increased fledging success and larger clutch sizes. In addition, higher nest box temperatures during incubation were related to heavier fledglings. This suggests that birds are also successfully able to allocate energy from one breeding stage to another. Thermal variations facilitated by restoration treatments might thus prove a valuable tool to aid avian breeding success.